Dosing Cefepime for Renal Function Does Not Completely Prevent Neurotoxicity in a Patient With Kidney Transplant. Issue 2 (June 2018) - Balderia, Percy Guanzon; Chandorkar, Aditya; Kim, Yongwoo; Patnaik, Soumya; Sloan, Joshua; Newman, George Charles
Abstract : Abstract: Dosing cefepime for renal function does not completely prevent neurotoxicity in a kidney transplant patient. Cefepime neurotoxicity has been reported primarily among patients with renal insufficiency who received standard doses of the antibiotic. We report a case of nonconvulsive status epilepticus from dose-adjusted cefepime in a kidney transplant patient. The timing of symptoms along with clinical and electroencephalographic improvement after discontinuation of cefepime was critical to the diagnosis. Whether we should adjust the dose of cefepime differently in a patient with transplanted kidney to prevent neurotoxicity is unknown.